Systematic Literature Review: Aplikasi Siskeudes Meningkatkan Kualitas Akuntabilitas Keuangan Desa Dan Kinerja Perangkat Desa - Putu Dhika Yahya Lajaba; Moh. Halim; Rendy Mirwan Aspirandi (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to provide a systematic literature review on the factors that influence the Siskeudes application to improve the quality of village financial accountability and the performance of village officials. This study uses a qualitative approach to document research with a systematic literature review as a research data analysis tool. The systematic literature review process consists of three stages, namely planning, implementation, and reporting. The initial study found 460 articles, the study used 12 articles based on inclusion and exclusion criteria for further analysis. There is data extraction that can answer research questions. The results of a systematic literature review from journals from 2015 to 2021 stated that the factors influencing the Siskeudes application to improve the quality of village financial accountability and the performance of village officials were the data input process, application use, information technology infrastructure, human resources, budget and financial knowledge. village, village budget preparation, transparency, and financial reports. The main influencing factors are the process of inputting data and using applications where the village government must provide education and training on a regular basis, coordinate with assistants and trainers from the center, provide support and motivation for staff/employees in the learning process, provide adequate facilities and infrastructure. will be used to improve human resources.